Comparison of participants and non-participants in a trial of induction versus expectant monitoring for intrauterine growth restriction at term (the digitat trial). (18th April 2012) - Boers, KE; Thornton, JG; Scherjon, S
Abstract : Background: The Disproportionate Intrauterine Growth Intervention Trial at Term (DIGITAT) compared induction with expectant management. In this secondary analysis we compared the outcomes of participants with non-participants. Methods: All patients who declined randomisation, but authorised data use were studied. Main outcomes; composite of perinatal death, 5-min Apgar score < 7, umbilical pH <7⋅05 or admission to neonatal intensive care; operative delivery. All comparisons were between participants and non participants, regardless of trial allocation or treatment received. Propensity scores were used to adjust for baseline differences between the randomised and non randomised women. Results: There were 650 randomised, and 452 non-participant women. Non-participants were older, smoked less, and had a lower BMI, and higher level of education. A total of 37 (6%) infants of participants experienced the composite adverse neonatal outcome, compared with 32 (8%) in the non-participants (difference -2% [95% CI -4%; 2%]). Caesarean sections were performed on 90 (14%) participants and 71 (16%) in the non-participants (-2% [95% CI -6%; 2%]). Among non-participants 3 (0.7%) deaths (2 stillbirths, 1 neonatal death) occurred. There were none in the randomised group. Interpretation: Despite better baseline health status there was a trend towards more adverse outcomes among non-particpants. This trial may be another example of the overall benefits of trial participation. Funding: ZonMw, the Netherlands, project number 945-04-558.